A fast mobile early warning system for water quality emergency risk in ungauged river basins. (November 2015) - Wang, Yonggui; Zhang, Wanshun; Engel, Bernard A.; Peng, Hong; Theller, Larry; Shi, Yingyuan; Hu, Shan
Abstract: Environmental decision support system (EDSS) has become an important research topic in the fields of water environment protection and emergency early warning. Most existing systems require plenty of measured data, which are typically unavailable in ungauged basins. In order to develop an early warning system that can work with few measured data, a mobile environment decision support system (MEWSUB) for early warning and emergency assessment in ungauged river basins was developed. A one-dimensional water quality model was built for the system and the terrain module and pollutant module were developed for terrain digitization and pollutant release process data generation. MEWSUB can quickly create water quality model input files, simulate the temporal release of pollutants, and display the results in a dynamically rendered map and trend line diagram via HTML5. The system has been used successfully to support early warning efforts during accidents on several ungauged rivers in China. Graphical abstract: Highlights: A mobile Early Warning System in Ungauged River Basins (MEWSUB) for water quality early warning is presented. A One-dimensional water quality model is used in MEWSUB because lack of data in ungauged river basins. MEWSUB can work with little measured data for coupling with automatic data generational methods. The system is successfully used to support early warning efforts on several ungauged rivers in China.